Islamic Religious Education in the Indonesia Gold 2045 Framework: A Literature Review on Strengthening Moderate Character and Nationalism from an Islamic Education Statistics Perspective - Nur Rochbani, Ita Tryas; Maulida, Ghina Rahmah; Firmansyah, Mohammad; Suratin, Sonia Isna; Munawarsyah, Muzawir (Universitas Islam Negeri Raden Intan Lampung, 2026)
Islamic Religious Education (IRE) plays a crucial role in fostering religious moderation and strengthening national character, which is essential for achieving Indonesia's Vision 2045. This study aims to explore how IRE can contribute to the development of moderate religious values and national commitment in students by analyzing the current practices and identifying gaps in existing educational frameworks. A qualitative research design with a literature review approach was employed to systematically map, explore, and synthesize relevant studies on IRE and religious moderation. The findings show that IRE plays a central role in promoting social cohesion and preventing religious-based conflicts, yet the integration of religious moderation values into the formal curriculum remains insufficient. The study also highlights the need for a more structured approach to incorporating religious moderation in educational content, teacher training, and assessment tools. This research provides a comprehensive analysis of how IRE aligns with the broader goals of Indonesia's Vision 2045 and offers practical recommendations for enhancing IRE’s role in building a tolerant, inclusive, and nationally committed generation. The novelty of this study lies in its integrative approach, which bridges IRE with contemporary challenges posed by digital media and social transformation, providing valuable insights for future curriculum development and policy-making in Indonesia.